Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.15376/biores.16.3.5467-5480
|View full text |Cite
|
Sign up to set email alerts
|

Properties of 3D-printed wood sawdust-reinforced PLA composites

Abstract: Thermal, morphological, and mechanical properties of three-dimensional (3D) printed polylactic acid (PLA) composites reinforced with different amounts of waste pine sawdust were investigated. To determine the mechanical properties of the obtained filaments, test samples were produced using a 3D printer according to the mechanical test standards. The filaments that were produced from blends that contained the wood sawdust at the highest level (20%) could be printed via a 3D printer without any problems. Accordi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…In this study, the tensile strengths generally decreased with the addition of wood flour to neat PLA polymer. Similarly, it has been reported that the tensile strength decreases due to the weak interface bonding as a result of the addition of wood/plant fiber to the neat PLA polymer (Stoof et al 2017;Petchwattana et al 2019;Kain et al 2020;Narlıoğlu et al 2021). As a result of the comparison of the tensile strengths of the composites, it was seen that the MWF-added composites (MPS1 and MPS2) showed better values than the UMWF-added composites (PS1 and PS2).…”
Section: Mechanical Properties Of 3d-printed Samplesmentioning
confidence: 58%
See 2 more Smart Citations
“…In this study, the tensile strengths generally decreased with the addition of wood flour to neat PLA polymer. Similarly, it has been reported that the tensile strength decreases due to the weak interface bonding as a result of the addition of wood/plant fiber to the neat PLA polymer (Stoof et al 2017;Petchwattana et al 2019;Kain et al 2020;Narlıoğlu et al 2021). As a result of the comparison of the tensile strengths of the composites, it was seen that the MWF-added composites (MPS1 and MPS2) showed better values than the UMWF-added composites (PS1 and PS2).…”
Section: Mechanical Properties Of 3d-printed Samplesmentioning
confidence: 58%
“…In addition, the tensile modulus first decreased with the addition of 10% wood flour to PLA polymer, then it increased with the addition of 20% wood flour, and it showed similar values with that of neat PLA. Similarly, it has been reported that the tensile modulus first decreases and then increases as a result of adding wood flour to PLA polymer (Stoof et al 2017;Estakhrianhaghighi et al 2020;Narlıoğlu et al 2021). The tensile strength of 3D-printed samples from neat PLA was 42.27 MPa, and the tensile modulus was 2.27 GPa.…”
Section: Mechanical Properties Of 3d-printed Samplesmentioning
confidence: 62%
See 1 more Smart Citation
“…The components of the wood material were responsible for the increase in peak intensities in these wavelength ranges. 48 It originates from carbonyl groups and water in the peak wood at a wavelength of 1640 cm À1 . In addition, the peak at a wavelength of 3430 cm À1 is due to the -OH stretching of nano MgO.…”
Section: Resultsmentioning
confidence: 99%
“…Sawdust or similar residues from the wood industry can be used as a valuable waste source for the production of high-quality 3D polymer materials. A recent study by Narlıoğlu and co-authors concludes that waste pine sawdust is a suitable reinforcing material for the production of composite filament for 3D-printing applications; it can be extruded with PLA polymer [ 15 ] but also other components, wood flour, lignin [ 16 ] and cellulose nanofibers, are being explored as functional additives and reinforcements in thermoplastic and thermoset matrices used in additive manufacturing (AM) or 3D printing [ 1 ]. The advantages of blending wood into PLA include improved biodegradability, high stiffness and low density compared to pure PLA polymer [ 17 ].…”
Section: Possible Additive Technologies To Be Used With Woodmentioning
confidence: 99%